Numerical Simulation on Effect of Separator Thickness on Coupling Phenomena in Single Cell of PEFC under Higher Temperature Operation Condition at 363 K and 373 K - Akira Nishimura; Daiki Mishima; Kyohei Toyoda; Syogo Ito; Mohan Lal Kolhe (Energies, 2023)
In hydrogen energy systems, the polymer electrolyte fuel cell (PEFC) is an important component. The purpose of this study is to clarify the effect of separator thickness (s.t.) in PEFC on the distributions of mass such as H2, O2, H2O and current density when PEFC is operated at 363 K and 373 K. The relative humidity (RH) of supply gases also impacts the operation. The numerical simulation (using a 3D model) with COMSOL Multiphysics has been conducted to analyze the characteristics of PEFC. It has been observed that the molar concentration of H2 using s.t. of 2.0 mm is smaller compared with the thinner s.t. cases at the initial operation temperature of a cell (Tini) = 363 K and 373 K. The molar concentration of O2 using s.t. of 2.0 mm is smaller compared with the thinner s.t. cases at Tini = 373 K, as well as the case for the RH of supply gases at the anode of 40%RH and cathode of 40%RH (A40%RH/C40%RH) irrespective of Tini. Additionally, it has been clarified that the molar concentration of H2O maintains a low value along with the gas channel at Tini = 373 K using s.t. of 1.5 mm and 1.0 mm. Moreover, it has been clarified that the current density using s.t. of 2.0 mm is the highest among the different s.t. irrespective of Tini, which is the most remarkable in the case of A40%RH&C40%RH.